Effect of unsaturated polyester concentration on rheological characteristics of polypropylene-unsaturated polyester reactive blend (Chemical Engineering Research Bulletin, 2010)
Reactive blends of polypropylene and unsaturated polyester with different compositions were prepared by melt processing using dicumyl peroxide (DCP) as initiator in a plasticoder. Rheological Characteristics of the blends were studied as a function of unsaturated polyester concentration over a range of strain rate. The possibility of forming a graft polymer increased with increasing the unsaturated polyester content. Change in viscosity behavior of the blends was a result of the competing reactions of degradation and grafting.Keywords: DCP; strain rate; degradation; graftingDOI = 10.3329/cerb.v14i2.5955 Chemical Engineering Research Bulletin 14 (2010) 105-108